Дослідження зміни параметрів відеоадаптеру портативного комп’ютеру на продуктивність в мультимедійних програмах - Орлов, Д. І.; Козловець, С. О. (ХНУРЕ, 2024)
This work investigates the effect of overclocking on the performance of the video adapter, focusing on the parameters of the clock frequency, the voltage of the GPU and video memory, as well as on the power limits. Using a Gigabyte GTX970 G1 Gaming graphics card and MSI Afterburner software for tuning, the work analyzes system stability and thermal performance during overclocking using the AIDA64 GPGPU Benchmark to evaluate performance. The findings of the study demonstrate the effect of overclocking on FPS in test tasks that are close to real scenarios using graphics programs and games.
Keywords: відеоадаптер; портативний комп’ютер